Classification of CM chondrite breccias—Implications for the evaluation of samples from the OSIRIS‐REx and Hayabusa 2 missions. (25th May 2020) - Lentfort, Sarah; Bischoff, Addi; Ebert, Samuel; Patzek, Markus
Abstract: CM chondrites are complex impact (mostly regolith) breccias, in which lithic clasts show various degrees of aqueous alteration. Here, we investigated the degree of alteration of individual clasts within 19 different CM chondrites and CM‐like clasts in three achondrites by chemical analysis of the tochilinite‐cronstedtite‐intergrowths (TCIs; formerly named "poorly characterized phases"). To identify TCIs in various chondritic lithologies, we used backscattered electron (BSE) overview images of polished thin sections, after which appropriate samples underwent electron microprobe measurements. Thus, 75 lithic clasts were classified. In general, the excellent work and specific criteria of Rubin et al. (2007) were used and considered to classify CM breccias in a similar way as ordinary chondrite breccias (e.g., CM2.2‐2.7). In BSE images, TCIs in strongly altered fragments in CM chondrites (CM2.0‐CM2.2) appear dark grayish and show a low contrast to the surrounding material (typically clastic matrix), and can be distinguished from TCIs in moderately (CM2.4‐CM2.6) or less altered fragments (CM2.7‐CM2.9); the latter are bright and have high contrast to the surroundings. We found that an accurate subclassification can be obtained by considering only the "FeO"/SiO2 ratio of the TCI chemistry. One could also consider the TCIs' S/SiO2 ratio and the metal abundance, but these were not used for classification due to several disadvantages. Most of the CM chondrites are finds that have suffered terrestrial weathering in hot and cold deserts. Thus, the observed abundance of metal is susceptible to weathering and may not be a reliable indicator of subtype classification. This study proposes an extended classification scheme based on Rubin's scale from subtypes CM2.0‐CM2.9 that takes the brecciation into account and includes the minimum to maximum degree of alteration of individual clasts. The range of aqueous alteration in CM chondrites and small spatial scale of mixing of clasts with different alteration histories will be important for interpreting returned samples from the OSIRIS‐REx and Hayabusa 2 missions in the future.